2017
DOI: 10.17576/jsm-2017-4612-21
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Silver Nanoparticles-based Sensing Probe for the Detection of Japanese Encephalitis Virus Antigen

Abstract: A novel silver nanoparticles (Ag NPs)-based optical sensing probe has been developed for the detection of Japanese Encephalitis virus (JEV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Under optimum conditions, namely 20 minutes of incubation time and 50 µg/mL JEV antibody was used, Ag NPs-modified SPCE biosensor strips exhibited LOD of 2.60 ng/mL to JEV antigen, with an analysis assay time of 20 min. The LOD of 2.60 ng/mL to JEV antigen of this work is much lower as compared to the Ag NPs sensing probe with LOD of 12.8 ng/mL reported previously [12].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Under optimum conditions, namely 20 minutes of incubation time and 50 µg/mL JEV antibody was used, Ag NPs-modified SPCE biosensor strips exhibited LOD of 2.60 ng/mL to JEV antigen, with an analysis assay time of 20 min. The LOD of 2.60 ng/mL to JEV antigen of this work is much lower as compared to the Ag NPs sensing probe with LOD of 12.8 ng/mL reported previously [12].…”
Section: Discussioncontrasting
confidence: 60%
“…Ag NPs exhibited excellent conductivity property and is used to enhance the performance of a glucose biosensor [11]. Our research group has attempted to fabricate an optical JEV biosensor by coating of silver nanoparticles onto glass substrates [12].…”
Section: Introductionmentioning
confidence: 99%
“…As a noteworthy example to illustrate this concept, Vinayagam et al reported the use of triangular AgNPs (TAg) that were oligomerized with a ssDNA probe, designed complementary to the target RNA sequence of a specific Dengue virus strain, that could distinguish between different serotypes of dengue virus strains [147] . Parallelly, DNA tetrahedrons crosslinked with AgNP probes for the detection of HIV virus [148] and sandwich based AgNP optical immunosensors for the detection of Japanese encephalitis Virus (JEV) antigens have been fabricated as well, by the immobilization of JEV antibodies on AgNPs that were deposited on amine functionalized glass sides [149] …”
Section: Agnps In Clinical Diagnosis Of Viral Infectionsmentioning
confidence: 99%
“…Exploiting the surface plasmon resonance (SPR) property of silver nanoparticles (AgNPs), an optical based sensing probe was fabricated with synthesised AgNPs drop casted onto (3-Aminopropyl)triethoxysilane (APTES) amine functionalized glass immobilised with JEV antibodies. Changes in the absorbance of light was detected upon binding of target JEV antigen (Ag) and analysed which resulted in a detection limit of 12.8 ng/ml (Lim et al 2017 ). Similarly, an optical Lateral Flow Assay (LFA) was developed for detecting JEV antibodies (Ab) in swine serum for sero-surveillance and mass screening using the SPR properties of AuNPs.…”
Section: Biosensors For Jev Diagnosticsmentioning
confidence: 99%